Social Reinsurance : A New Approach to Sustainable Community Health Financing - Dror, David M.; Preker, Alexander S. (Washington, DC: World Bank and Geneva: International Labour Office, 2013)
Including health issues at the top of the political agenda, is an indictor for national development. Breaking the vicious cycle of low resources leading to illness, and illness leading to poverty, is a problem that all policy makers face in poor countries. Access to decent and affordable health care is to be facilitated by community-based institutions, which require sustainability through social reinsurance. The authors offer a concept as promising as original, opening a path between traditional government-based, and market-based responses to the lack of health care for the very poor, while maintaining a role for the government, in furthering social goals, through micro-insurance, but also creating a favorable market environment. The path is a pragmatic look at what close-to-people-needs schemes can do to fill the gap of ill-being. The authors, however, dig deeper into the subject in various manners: they link their analysis to the emerging study of social capital, and the need for people to trust their peers, and build networks with them; they also give a strong analytical underpinning to how to insure, and reinsure community-based financing schemes; they preempt possible critics, by addressing the need to design early on, an adequate regulatory framework for micro-insurance, and reinsurance; and, they go from theory to practice, with a thorough case study of a pilot experience in the Philippines.